(untitled) (FEATURES AND PROBLEMS OF IMPLEMENTING ECONOMIC REFORMS IN AZERBAIJAN, 2025)
The article comprehensively analyzes the legal foundations and regulatory mechanisms of digitalization processes, which are among the priority directions of modern economic development. Digitalization is evaluated not merely as a technological renewal of economic activity, but as a multifaceted process that requires the formation of management relations, legal norms, and social institutions on new principles. As a result of the formation of the digital economy, such concepts as e-government, digital trade, artificial intelligence, and big data have become integral parts of economic circulation and legal relations. The author notes that although digital transformation processes are developing rapidly, their legal regulation in Azerbaijan’s legislative system remains at an early stage. The existing normative-legal acts are mainly fragmentary in nature and do not fully ensure the comprehensive management of digitalization. Thereforethe preparation of systematic and scientifically grounded legal concepts, as well as the integration of international experience into national legislation, emerge as important tasks. The article also emphasizes that the lack of precise legal norms in areas such as artificial intelligence, cybersecurity, the legal circulation of digital assets, and data protection limits the development of the digital economy. Nevertheless, the existing legal framework provides an important platform for future reforms. In the coming years, it is necessary to form a unified legal policy in this field, and develop digital law as an independent institution, and harmonize the normative-legal system with international standards.